Perancangan Toko Online Di Ozzome.ink - imam al hakim; Chairullah Naury; Eka Budhi Santosa (Indonesian Journal of Information Technology and Computing (IMAGING), 2023)
The store itself is one of the public spaces that is used as a place of business that is itself as an activity to display, store, and sell, as well as a meeting area between entrepreneurs and consumers who can make a profit for the manager and owner (Haryanto et al., 2022). Ozzome.ink is a store that sells various types of shirts. The sales system that still relies on the manual system is still valid in this store. Admin Ozzome.ink makes sales by recording sales data into books or notes only. This can cause nominal amount errors when making sales data reports. In addition, this manual method also makes buyers wait long enough to make payments. Based on the description of the background mentioned above, it can be formulated the problem to be solved in this study is â€how to design an online store in Ozzome.inkâ€. The limitation of the problem that the author discusses in the study focuses more on the process of recording sales data in the scope of Ozzome.ink. The method used for designing online stores uses the Software development Life Cycle (SDLC) with the Waterfall model. The programming language used to design the online store is Native PHP and MySQL database as a medium for storing data.